Diseño de un manual de control interno para la fábrica de lácteos amazonas ubicada en el cantón Latacunga provincia de Cotopaxi durante el periodo 2016 - Defaz Pallo, Víctor Alfonso (2016)
The investigation have as primordial finality design an internal control manual for the Amazonas Dairy factory since it is a fundamental tool to correct failing of administrative and operative process within the institution, fits to mention what an Internal Control adequate help to protect the existing resources from an organization, also it helps develop operational activities efficiently and orderly. To conduct the research the following methods were applied; inductive, deductive, analytics and descriptive to get an real and objective information also are used techniques of collection as surveys and interview which detected some observations in the factory on the other side for a best understanding of the results obtained was performed the analysis and interpretation of the results….